Whole-genome sequencing-based source tracing and infection control of Serratia marcescens blood culture events in pediatric patients - Zhang, Wang; Ma, Caihua; Xu, Falin; Zhao, Chenjing; Wang, Ling (Frontiers in Microbiology, 2026)
ObjectiveSerratia marcescens (S. marcescens) is an opportunistic pathogen increasingly associated with nosocomial infections in immunocompromised pediatric patients. This study aimed to investigate the epidemiological and molecular epidemiological characteristics of S. marcescens-positive blood cultures and to provide evidence for targeted infection prevention strategies.MethodsEleven cases of S. marcescens-positive blood cultures were identified across eight pediatric wards of a tertiary hospital in China in October 2024. Clinical and microbiological assessments were conducted to distinguish true infections from contamination. Antimicrobial susceptibility testing was performed, and whole-genome sequencing (WGS) was used to characterize resistance, virulence, and plasmid replicons. Core genome single-nucleotide polymorphism (SNP)-based phylogenies, Bayesian temporal inference, and transmission tree reconstruction were used to explore genetic relatedness, transmission dynamics, and cryptic cases.ResultsTwo cases were diagnosed as hospital-acquired sepsis, while nine were classified as contamination. The isolates exhibited intrinsic resistance to first- and second-generation cephalosporins but remained susceptible to carbapenems. Seven resistance genes—including aac(6’)-Ic, oqxB, and tet(41)—and four virulence genes, including cheY and fliM, were identified. Nine isolates carried IncFII-type plasmids. Core genome SNP analysis revealed minimal genetic divergence, with the most recent common ancestor traceable to late 2023, suggesting approximately 10 months of silent transmission. Transmission tree inference further indicated the presence of undetected cryptic cases. Following the implementation of bundled interventions—including sink replacements and disinfectant use, reinforcement of hand hygiene, and environmental decontamination—no new cases occurred during 1 month of follow-up.ConclusionThis study identified a highly clonal S. marcescens cluster with evidence of prolonged, unnoticed circulation and cross-ward transmission in the pediatric units. These findings underscore the hidden persistence of this pathogen in the hospital environment and the need for strengthened infection control measures.